Síndrome do intestino irritável: tratamento convencional e terapia cognitivo-comportamental - Zanin, Carla Rodrigues (2015)
Irritable Bowel Syndrome (IBS) is a chronic gastrointestinal disorder that causes significant impairment on the patients´ quality of life. It is associated with anxiety, depression and stress. The objective of this study was to evaluate the impact of cognitive-behavioral therapy (CBT) associated with the conventional treatment of IBS . Fourteen adult patients (21 and 65 years old) participated in the study. They were attended once in a week during four months and had a six month-follow up in the outpatient clinic of a school hospital in the interior of São Paulo state . A convenience sample for the intervention groups (cognitive-behavioral therapy - CBT) and control (Conventional Treatment – CT) was used as selection standard. Hospital Scale of Anxiety and Depression ; Inventory of Stress-Related Symptoms; Scale of Modes Coping Problems; Quality of life; Visual Analog Scale (VAS ) and a register with sociodemographic data were used. Patients in both groups showed symptoms of anxiety, depression and stress, with reduction of symptoms in the evaluation after the four months and their follow up , in the CBT with significant clinical improvement of anxiety and depression and stress symptoms. No significant changes were observed in pre- and follow up of the CT G according to the symptoms of anxiety, depression and pain. All patients in both groups had pain at baseline, with a reduction in pain intensity in the post (4 months) at follow up (6 months), in the CBT, showing significant difference. At follow up (TC G and CBT G) a significant difference pointing out a decrease of pain complaints after psychological intervention in CBT G, suggesting that CBT has shown efficacy on the pain control treatment of IBS patients . Most of quality of life domains were assessed as unsatisfactory for both groups, with clinical improvement in post intervention assessment and follow up, in the CBT G. Comparing the follow up of the CT G and CBT G, data showed significant differences in the domains functional capacity, physical aspect, social aspect and emotional aspect, pointing out that psychological intervention plays an important role in the control and reduction of physical and emotional symptoms as well as showing significant difference in pre- and post intervention and pre and follow up in the CBT G. The least used coping strategy was facing the problem and social GTC in the pre and follow-up, the CBT G, the social confrontation was the least used in the pre. However, there was acquisition of coping strategies observed in post evaluation (4 months) and follow up (6 months) in the GTCC. The results showed some anxiety, depression, stress and impaired quality of life in this sample as well as positive impact of CBT for the control of physical and emotional symptoms and improvement in the quality of life and acquisition of coping strategies, demonstrating the need for appropriate intervention for patients with IBS.